2022
DOI: 10.1007/s12665-022-10680-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the contamination of the subsurface and groundwater by monoaromatic hydrocarbons in an eastern Amazonian town in northern Brazil

Abstract: The present study evaluated the contamination by monoaromatic hydrocarbons (BTEX: benzene, toluene, ethylbenzene, and xylene) of the subsurface of gas stations and adjacent residences in the Amazonian town of Bragança, in northern Brazil. We combined the ground penetrating radar (GPR) geophysical tool, to detect possible plumes of contamination by BTEX, with gas chromatography (GC) and mass spectrometry (MS), which were used to diagnose the presence of BTEX in water samples obtained from boreholes located with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…Ref. [67] evaluated the occurrence of BTEX contamination in the subsoil of gas stations and adjacent residences in the eastern Amazonian town of Bragança, combining groundpenetrating radar (GPR) with GC/MS. That study identified the presence of the BTEX contaminants benzene, toluene, ethylbenzene, and/or xylene in 13 of the samples of underground water (19.7% of the total) and found evidence of the possible existence of plumes of BTEX contamination in the subsurface of the gas stations, confirming that leaks in the storage tanks were the source of the contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [67] evaluated the occurrence of BTEX contamination in the subsoil of gas stations and adjacent residences in the eastern Amazonian town of Bragança, combining groundpenetrating radar (GPR) with GC/MS. That study identified the presence of the BTEX contaminants benzene, toluene, ethylbenzene, and/or xylene in 13 of the samples of underground water (19.7% of the total) and found evidence of the possible existence of plumes of BTEX contamination in the subsurface of the gas stations, confirming that leaks in the storage tanks were the source of the contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, it is important to consider that even a minimal level of contamination serves as a warning call, which highlights the need for continued monitoring. Further research is also needed to identify the source of the contamination of the subsurface in the two study towns, using, for example, geophysical tools, which have been shown to be highly effective for the identification of underground plumes of BTEX contamination, contributing to the verification of possible sources of contamination, e.g., [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Geophysical tools are one other valuable option for the description of the quality of soils. This technology is non-invasive, non-destructive, and has excellent spatio-temporal resolution (e.g., [22][23][24]), and can provide valuable information on the characteristics of the subsoil, including its lithology, stratigraphy, bedrock, water table, and the presence of depressions, faults, and fractures (e.g., [25][26][27][28][29][30][31][32][33][34][35][36][37][38]).…”
Section: Contributionsmentioning
confidence: 99%
“…The data were also edited, with spatial resampling and interpolation being applied to the traces. The data processing involved the following steps (e.g., [25][26][27][28][29][30][31][32][33][34][35][36][37][61][62][63][64]): static correction of zero-time, gain, time filtering (1D), and spatial filtering (2D), that is, background removal and moving average trace subtraction. The hyperbole overlap method was used for the time-depth conversion, by obtaining a propagation velocity of 0.092 m/ns.…”
Section: Standard Penetration Testmentioning
confidence: 99%